Numerical investigation on the swirler parameters for an axial liquid-liquid hydrocyclone. Issue 1 (February 2021) - Zhan, Min; Cheng, Xinping; Yang, Wanyou; Zhang, Fenghui; Guo, Peiwen; Shen, Qiong
Abstract: The exploitation of most oil fields has entered the middle and late stages and the proportion of water in the mixture extracted from the oil fields at this stage is very high, even reaching 80%-90%. In order to lower the cost of exploitation and make the oil field more sustainable, oil and water separation needs to be carried out downhole. The downhole space is small, and the separation device should be small and efficient. Therefore, this paper studies the axial flow oil-water separator that can be used for downhole oil-water separation. Study the influence of swirler structural parameters on the velocity field in the separator, and find structural parameters that are more beneficial to oil-water separation. The results show that increasing the outlet angle of the guide vane, the twisted diameter of the blade and the number of blades can all increase the tangential velocity of the flow field in the separation section, and generate centrifugal force to promote the aggregation of light fluid towards the center.